Chile : Financial Sector Assessment Program-Detailed Assessment of Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies. (IMF Staff Country Reports; Country Report ;, 2004)
This paper focuses on key findings of the Detailed Assessment of Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies on Chile. The assessment reveals a high degree of compliance with the Transparency Code, including in the objectives and responsibilities of the central bank. The target and instrument autonomy of the Central Bank of Chile is strong by virtue of being enshrined in the constitution. The process for monetary policy formulation, implementation, and communication is highly transparent.